Modelo de Gestión de Calidad para la Florícola AGRINAG S.A., de la provincia de Cotopaxi - Viteri Ortiz, Katiana Del Carmen (2021)
Productivity at the business level has become a strategic element whose directionality focuses on maximizing the levels of efficiency and effectiveness in all areas that make up a business. The versatility to combine with other components such as quality allows the development of management models that optimize operational activities, thus improving the functionality and performance of organizations. The objective of this research was to design a Quality Management model that optimizes the productivity of Florícola AGRINAG S.A., in the province of Cotopaxi. The study was framed in a quantitative approach, descriptive type, basic modality; with a population and finite sample of 26 workers. The techniques used to collect the information were direct observation and interview. The results made it possible to identify the presence of weaknesses, as well as the absence of quality control management mechanisms linked to international standards that affect the entire production system. This led to proposing the Quality Management design, based on the European excellence model EFQM (European Business Excellence Model), defining, describing and explaining each step or phase to follow. The conclusions revealed that AGRINAG SA, despite having a Quality Management System based on national and international standards and norms, does not have a program that allows it to evaluate and qualify the quality of the processes, this represents a limitation to carry out the execution. of strategic plans around actions that affect both productivity and quality.